The neuroscience of depressive disorders: A brief review of the past and some considerations about the future - Kaltenboeck, A; Harmer, C (SAGE Publications, 2018)
Depression is a common and debilitating mental health condition whose underlying aetiology and pathophysiology is still relatively poorly understood. In this article, we first turn to the past and briefly review what neuroscientific investigations have taught us so far about depression. In doing so, we cover neurochemical, neuroendocrine, immunological, functional and structural anatomical, and cognitive levels of description. We then turn our attention to the future and discuss where the field might be moving in the years to come. We argue that future developments may rely on three important lines of enquiry: first, the development of an integrated neuroscientific model of depression and its treatment in which different levels of description can be mechanistically linked, and in which distinct pathophysiological trajectories leading to depressive symptomatology can be identified. Second, the continued search for potentially overlooked pathophysiological factors, especially outside the immediate boundaries of the brain. And third, the improvement in translation of neuroscientific insights to aid and advance clinical practice and research.